Analysis of Parking Tax and Parking Levy Revenue in Medan City - Elsa Nasution; Yunita Sari Rioni; Ayu Kurnia Sari (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study analyzes parking tax revenue and its contribution to increasing Local Own-Source Revenue (PAD) of Medan City during the 2014–2018 period. The research employs a descriptive quantitative and qualitative approach to identify the tax collection system, effectiveness, constraints, and optimization efforts. Data were obtained from documentation of the Regional Tax and Retribution Management Agency (BPPRD) and in-depth interviews with officials. The findings show that parking tax revenue achievement fluctuated. Major obstacles include low taxpayer awareness, limited human resources, and weak supervision systems.